Major Intrahepatic Veno-Venous Fistula after Fontan Operation Treated by Transcatheter Implantation of Amplatzer Septal Occluder through Internal Jugular Vein - Guzeltas,Alper (2016)
Abstract Six months after undergoing a Fontan operation, a 7-year-old boy with right atrial isomerism and a single functional ventricle was admitted to our emergency department with cyanosis. Emergency cardiac catheterization revealed a large veno-venous fistula that began in a left hepatic vein, connected to the left accessory hepatic veins, and drained into the common atrium, resulting in desaturation. The fistula was occluded proximally with an Amplatzer septal occluder, with satisfying results; the patient's systemic arterial saturation decreased during his hospital stay. Three weeks after the first intervention, a second procedure was performed to retrieve the first device and to close the fistula distally. Multiple attempts with different types of gooseneck snares and a bioptome catheter failed to retrieve the first device, so a telescopic method was used to re-screw it. Using a Mullins long sheath and delivery sheath, the delivery cable was manipulated to fit into the slot of the end screw, and the cable was rotated gently in a clockwise direction to re-screw the device. Then, another Amplatzer septal occluder was placed at the distal end of the fistula. In conclusion, distal transcatheter occlusion of intrahepatic veno-venous fistulas might lead to better clinical outcomes in selected patients. Amplatzer septal occluder device can be retrieve without any complication within three weeks.